PENGARUH CAPITAL ADEQUACY RATIO, PENYALURAN KREDIT DAN NON PERFORMING LOAN TERHADAP PROFITABILITAS - Atmaja Negara, I Putu Agus; Sujana, I Ketut (E-Jurnal Akuntansi, 2014)
There several ratios that affect the profitability of a bank of which the CAR, NPL. NPL can weaken the influence CAR and lending to profitability. The purpose this study analyze effect variable CAR and lending to profitability with NPL moderating variable. This research carried out the banks listed the Indonesia Stock Exchange 2010-2012 period, using purposive sampling method in sample collection. The results showed that partially CAR and NPL not affect the profitability, while lending positive effect profitability. While NPL negatively affect the profitability of the relationship between CAR and NPL positive effect on relationship between the profitability of lending.
Keywords: Profitability, CAR,Credit, NPL